The Influence of Leadership, Work Motivation and Organizational Culture on Job Performance - Wisetsri, Worakamol; Ud Din, Maaz (International Journal of Psychosocial Rehabilitation, 2020)
The education division is dynamic for the development of a country and requires teachers to offer and constrain assistance to improve it into an impending civilization. The target of this research is to study the result of leadership style, work motivation, and organizational culture discreetly on the job performance of visiting and pledged lecturers at the University of Swabi, KP-Pakistan. The random sampling was used in this research. This research was descriptive with explanatory research. The populations of this research consist of visiting and contractual lecturers working at the University of Swabi. The collected data were from a survey based on an interview with 70 visiting and contractual lecturers as section-over-assumption questionnaires. The findings of this research identify that guidance style, work motivation, and organizational culture suggestively result in the job performance of visiting/contractual lecturers.